Hematopoietic Stem Cell Biology - Kondo, Motonari; SpringerLink (Online service) (Totowa, NJ : Humana Press, 2010)
Hematopoietic Stem Cell Biology is the newest installment in the Stem Cell Biology and Regenerative Medicine series, to which it adeptly contributes as it offers a selection of carefully chosen topics so that the readers can understand recent advances in the field of the hematopoietic stem cells and hemato/lymphopoiesis. Each chapter is not a simple review of the topic, but rather an in-depth insight, which allows the reader to attain a multifaceted knowledgebase on hematopoietic stem cells. The chapters, which are authored by the leading experts in the field, cover characteristics of the hematopoietic stem cells at the cellular and molecular levels, offers details in regulatory mechanisms of differentiation mechanisms of hematopoietic stem cells to more mature blood cell, and discusses abnormal hematopoiesis that leads to leukemia. Hematopoietic Stem Cell Biology serves the inquiring minds of researchers, graduate students and post doctorate fellows as it expertly addresses the ever-growing field of hematopoietic stem cells and hemato/lymphopoiesis.
Principles of Hematopoietic Stem Cell Biology -- Hematopoietic Stem Cells and Their Niche -- Hematopoietic Stem Cells and Somatic Stem Cells -- Developmental Biology of Mammalian T-Cell Progenitors: From Early Lymphoid Progenitors to Thymus-Colonizing Cells -- GATA1 and GATA2 Function in Hematopoietic Differentiation -- Role of the IL-7 Receptor in gc(Se (BT-Cell Development from Hematopoietic Stem Cells -- Dendritic Cell Homeostasis: Physiology and Impact on Disease -- Wnt in Hematopoietic and Leukemic Stem Cells.s
Keywords: Medicine; Immunology; Hematology; Cytology; Developmental biology; Medicine & Public Health; Hematology; Immunology; Cell Biology; Developmental Biology